2021
DOI: 10.48550/arxiv.2106.00742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of Hate Speech automatic detection using Natural Language Processing

Abstract: With the multiplication of social media platforms, which offer anonymity, easy access and online community formation and online debate, the issue of hate speech detection and tracking becomes a growing challenge to society, individual, policy-makers and researchers. Despite efforts for leveraging automatic techniques for automatic detection and monitoring, their performances are still far from satisfactory, which constantly calls for future research on the issue. This paper provides a systematic review of lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 68 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…In this line of work, previous studies have used deep learning models, such as word embeddings [10,92] and several neural architectures [93,94]. Recent advances in NLP learning methods have used the transformer architecture [95], which has been applied to hate speech and similar content [96]. These mentioned approaches can be easily added to the intelligent engine due to the presented architecture and its corresponding semantic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…In this line of work, previous studies have used deep learning models, such as word embeddings [10,92] and several neural architectures [93,94]. Recent advances in NLP learning methods have used the transformer architecture [95], which has been applied to hate speech and similar content [96]. These mentioned approaches can be easily added to the intelligent engine due to the presented architecture and its corresponding semantic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the discussed papers and to understand the cutting edge in this area to track the latest approaches, resources, statistics, techniques, and methods, we will also consider recent survey papers. Specifically, narrative review papers ( Al-Hassan & Al-Dossari, 2019 ; Mishra, Yannakoudakis & Shutova, 2019 ; Schmidt & Wiegand, 2017 ), systematic review papers ( Fortuna & Nunes, 2018 ; Poletto et al, 2021 ) and more recent systematic review articles ( Jahan & Oussalah, 2021 ). In this section, we will discuss the proposed taxonomy, which covers five different aspects and tasks:…”
Section: Survey Methodologymentioning
confidence: 99%
“…On the other hand, there are some studies that investigate the available dataset for this area. For example, Jahan & Oussalah (2021) investigated 69 hate speech datasets and found that the existing efforts provided a variety of challenges in terms of dataset preparation. Generally, researchers begin by gathering and annotating new comments from social media or by referring to older datasets.…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…with a growth in the number of people using social media sites such as Twitter to express themselves [ 3 ]. The lack of tools and benchmark datasets are the main challenges in this field [ 4 ]. The goal here is to construct an accurate method for detecting misogyny and sarcasm from Arabic text.…”
Section: Introductionmentioning
confidence: 99%